HapticSnakes: multi-haptic feedback wearable robots for immersive virtual reality - Mohammed Al-Sada (14158872) (2019)
Haptic feedback plays a large role in enhancing immersion and presence in VR. However, previous research and commercial products have limitations in terms of variety and locations of delivered feedbacks. To address these challenges, we present HapticSnakes, which are snake-like waist-worn robots that can deliver multiple types of feedback in various body locations, including taps-, gestures-, airflow-, brushing- and gripper-based feedbacks. We developed two robots, one is lightweight and suitable for taps and gestures, while the other is capable of multiple types of feedback. We presented a design space based on our implementations and conducted two evaluations. Since taps are versatile, easy to deliver and largely unexplored, our first evaluation focused on distinguishability of tap strengths and locations on the front and back torso. Participants had highest accuracy in distinguishing feedback on the uppermost regions and had superior overall accuracy in distinguishing feedback strengths over locations. Our second user study investigated HapticSnakes’ ability to deliver multiple feedback types within VR experiences, as well as users’ impressions of wearing our robots and receiving novel feedback in VR. The results indicate that participants had distinct preferences for feedbacks and were in favor of using our robots throughout. Based on the results of our evaluations, we extract design considerations and discuss research challenges and opportunities for developing multi-haptic feedback robots. Other Information Published in: Virtual Reality License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10055-019-00404-x